PENGARUH PENGGUNAAN MEDIA E-LEARNING, MOTIVASI BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP KEMAMPUAN INTELEKTUAL (STUDI: MAHASISWA MAHASISWI DI UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA) - Jajuk Herawati; Didik Subiyanto; Nadela Sary (JURNAL ILMIAH EDUNOMIKA, 2021)
Campus academic life lies in the learning media and its environment. The role of the lecturer as a facilitator should be able to facilitate students and their students to find their own way of learning, which can be done without being limited by space and time. It is hoped that with this E-learning method, students and female students will be able to be more active and more creative in learning with the motivation to learn from themselves. This study aims to determine whether E-learning, Learning Motivation, and the Learning Environment affect Intellectual Ability. The research method used is a quantitative method and the data collection using a questionnaire. The results of the analysis show that the independent variable has a positive and significant effect on the independent variable.